Normal-to-plane surface plasmon mode for angle-and-polarization independent optomechanical sensing

KR103013949B1Active Publication Date: 2026-09-04SAMSUNG ELECTRONICS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020220060349
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-27
Filing Date
2022-05-17
Publication Date
2026-09-04
Estimated Expiration
2042-05-17

Smart Images

  • Figure 112022052217522-PAT00011_ABST
    Figure 112022052217522-PAT00011_ABST
Patent Text Reader

Abstract

Exemplary embodiments of the present invention generally relate to creating specific nanostructures on a substrate to improve the angular independence of surface plasmon resonance modes. This may include a metamaterial structure comprising nanostructures located on or within a pattern on the substrate. The nanostructures may be parabolic in shape and periodic.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] An exemplary embodiment of the present invention generally relates to creating specific nanostructures on a substrate to improve the angular independence of surface plasmon resonance modes. Background Technology

[0002] Measuring intraocular pressure can be challenging. Current technologies require expensive and cumbersome sensors. These sensors may require the eye to be fixed and positioned at a fixed angle of incidence. On the other hand, metamaterials, which may include plasmonic materials, hold the potential for various improvements over current methods, including reduced size and reduced angle dependence. Currently, metamaterials are not angle-independent and cannot be implanted in the eye. There is a need for angle-independent metamaterials or metamaterials with reduced angle dependence. The problem to be solved

[0003] The objective of the present invention is to provide the creation of specific nanostructures on a substrate to improve the angular independence of surface plasmon resonance modes. means of solving the problem

[0004] An exemplary embodiment of the present invention provides a metamaterial structure comprising a substrate and nanostructures positioned in a pattern on or within the substrate, wherein the nanostructures are paraboloid-shaped and periodic. An additional exemplary embodiment provides a method for manufacturing a metamaterial surface comprising depositing a nanostructure metal on a substrate and forming paraboloids from the nanostructure metal. Effects of the invention

[0005] The present invention provides a metamaterial structure comprising nanostructures patterned on or within a substrate. The nanostructures according to the present invention may be formed on a substrate to improve the angular independence of surface plasmon resonance modes. Brief explanation of the drawing

[0006] FIG. 1 illustrates an exemplary embodiment of a nanostructure of an exemplary embodiment of the present invention. Figure 2a shows a side view of the nanostructure of Figure 1. FIG. 2b illustrates a side view of a nanostructure of an exemplary embodiment of the present invention. FIG. 2c illustrates an experimental test based on experimentally varying height and diameter values ​​of the nanostructures of FIG. 1. Figure 3 illustrates an exemplary comparison of the nanostructures of Figure 1 of two different shapes. Figure 4 illustrates a manufacturing process for the production of the nanostructure of Figure 1. Figure 5 illustrates the manufacturing process of Figure 4. FIG. 6a illustrates an exemplary embodiment of a sensor in a top view. FIG. 6b illustrates an exemplary embodiment of the sensor in a side view. Figure 7 illustrates pressure measurements using changes in the peak wavelength of the reflection spectrum of Figure 2 of the structure of Figure 6 having the first nanostructure type and the second nanostructure type of Figure 3 at varying pressures. Specific details for implementing the invention

[0007] Metamaterials can interact with light in unconventional ways. Metamaterials may consist of arrays of nanostructures distributed across a surface. Spectra, such as the visible spectrum, may interact with these nanostructures. Plasmon materials may also be a type of metamaterial. There may be surface plasmon (SP) modes that can cause charge distributions on the nanostructured surface of a metamaterial, where the spectrum may oscillate periodically between positive and negative charges.

[0008] Surface plasmon modes may occur when nanostructures have specific shapes and distributions. In some embodiments, the nanostructures may have shapes such as paraboloids, and the distribution may include overlapping tiles that may have a hexagonal shape. Surface plasmon modes, also known as vertical-to-plane modes, may interact with the distribution of nanostructures to reflect another wavelength, known as the “reflection peak wavelength” or “target wavelength,” from the spectrum with an intensity much greater than the wavelengths. In many metamaterials, angles of incidence may change the reflection peak wavelength. However, due to paraboloid-shaped nanostructures and overlapping tile distributions, changes in the angle of incidence may result in a significantly lower change in the reflection peak wavelength compared to other shapes and distributions of nanostructures.

[0009] This significantly reduced dependence of the peak wavelength on the angle of incidence may lead to the term “angle independence” as used herein to describe this phenomenon.

[0010] Additionally, when a nanostructure is stretched or compressed, the reflection peak wavelength may change. This property of the reflection peak wavelength change can be used to measure pressure changes when the nanostructure is part of a pressure sensing device. Finally, a change in peak wavelength may also occur if the nanostructure is exposed to a liquid on its surface. The liquid may interact with the surface of the nanostructures to change the peak wavelength shift. This property of the peak wavelength shift change can also be used to identify chemicals in chemical analysis sensors.

[0011] Conventional processing techniques may allow shapes including disks and pillars, but there have been no techniques capable of allowing parabolic or other curved shapes that can be manufactured at the nanometer scale. As described, these processing techniques may enable vertical-to-planar mode nanostructures.

[0012] FIG. 1 illustrates an exemplary embodiment of a structure (100). The structure (100) may include nanostructures (101). The nanostructures (101) may be inserted inside a substrate (105) or may be on top of the substrate (105). The nanostructures (101) may be organized into a pattern (103).

[0013] In some embodiments, the nanostructures (101) may be gold, aluminum, silver, copper, aluminum-doped zinc oxide, indium tin oxide, titanium nitride, indium gallium arsenide, tungsten oxide, titanium-tungsten, or any other metal or metal alloy, but may also be made of other materials not listed. The nanostructures (101) may be positioned or distributed as a pattern (103) on or within a substrate (105). The pattern (103) may be periodic, which may be a repetitive distribution of the nanostructures. The pattern (103) may have equidistant nanostructures (101), such as a hexagonal pattern. Pattern (103) may have both equidistant and non-equidistant (i.e., partially equidistant) structures, such as a square pattern where some neighboring nanostructures may be equidistant while other neighboring nanostructures have different distances (e.g., diagonal neighbors). Pattern (103) may be periodic or semi-periodic, and may have a repeatable pattern in some parts of the nanostructures while having a non-repeatable pattern in other parts of the nanostructures.

[0014] In some embodiments, the pattern (103) may form a tessellation, which may be a tile. The tessellation may or may not overlap. The pattern (103) may be a periodic pattern that may provide equidistant spacing of the nanostructures (101). Equidistant spacing may be an approximation where the distance between the nanostructures is approximately equal but may have deviations due to accuracy limitations of manufacturing techniques, which will be described in more detail below.

[0015] In some embodiments, the pattern (103) may be six-sided, which may be a hexagonal tile pattern, also known as a hexagonal lattice. The nanostructures (101) may form a hexagonal tile pattern, and six nanostructures may form six vertices of the hexagon. In some embodiments, nanostructures (102a to 102f) may form the pattern (103) for exemplary cases of the hexagonal pattern. There may be additional nanostructures inserted inside the pattern (103), such as the center of the pattern (103), which may be a nanostructure (102g). The nanostructure (102g) may form a vertex of another pattern (103) of nanostructures.

[0016] The nanostructure (102a) may be located at a first distance (104) from the nanostructure (102b). The first distance (104) may also be known as a lattice constant and may be the distance between the center of the nanostructure (102a) and the center of the nanostructure (102b). Additionally, the nanostructure (102b) may be located at a first distance (104) from the nanostructure (102c). The first distance (104) may be based on the target wavelength of the structure (100), and the structure (100) may be designed for peak wavelength reflection, which will be described in more detail in FIG. 2. In some embodiments, the first distance (104) may be between 60 nm and 600 nm. In other embodiments, the first distance (104) may be larger for longer target wavelengths and smaller for shorter wavelengths.

[0017] The angle between the edges formed by nanostructure (102a) to nanostructure (102b) and nanostructure (102b) to nanostructure (102c) may be a first angle (106). In some embodiments, if the pattern (103) is hexagonal, the first angle (106) may be about 120 degrees. The first distance (104) and the first angle (106) may be approximately the same for all edges and angles of the pattern (103) for all subsequent nanostructures (102a to 102f).

[0018] In alternative embodiments, the shape of the pattern (103) may be any shape that can be tessellated. In some embodiments, the pattern (103) may maintain equidistant and equiangular properties for all nanostructures as previously described. In other embodiments, the pattern (103) may not have nanostructures that are completely equidistant and equiangular. In yet other embodiments, the pattern (103) may not be periodic, that is, it may be a fixed pattern in which the nanostructures (101) may not be equidistant from each other.

[0019] In some embodiments, the substrate (105) may be a flexible or stretchable material that may allow flexing of the substrate, such as polydimethylsiloxane (PDMS), but may be another material. In another embodiment, the substrate (105) may be rigid, such as nickel, but may be another material. In some embodiments, the substrate (105) may be 100 nm to 50 μm thick. As will be easily understood, the pattern (103) may alternatively be represented as a tiling of triangles (e.g., equilateral triangles or isosceles triangles) forming a hexagonal or square pattern.

[0020] FIG. 2a illustrates a side view (200) of the structure (100) of FIG. 1. The spectrum (201) may be moved onto the structure (100) at a first angle of incidence (203a), which may also be known as a first angle (203a). The first angle (203a) may be any angle between 0 degrees (parallel to the plane of the structure (100)) and 90 degrees (perpendicular to the plane of the structure (100)). In some embodiments, the spectrum (201) may include any wavelength or range of wavelengths, which may be known as broadband light in the visible spectrum to the near-infrared spectrum. In another embodiment, the spectrum (201) may be in a different spectral range, such as near-infrared, ultraviolet, microwave, or other wavelength ranges. There may be a second angle of incidence (203b) and a third angle of incidence (203c), which may be any angle between 0 and 90 degrees.

[0021] The spectrum (201) may interact with the structure (100) and may produce a reflection spectrum (202) that may be reflected from the structure (100) at a first reflection angle (204a). The first reflection angle (204a) may be any angle between 90 degrees (perpendicular to the plane of the structure (100)) and 180 degrees (parallel to the plane of the structure (100)). The reflection spectrum (202) may have a peak wavelength, which may also be known as the target wavelength, which may be reflected and all other wavelengths may be reflected, or may be hardly reflected or not reflected at all, which will be described in more detail below. There may be a second reflection angle (204b) and a third reflection angle (204c), which may be any angle between 90 degrees and 180 degrees. The first reflection angle (204a) may depend on the first incident angle (203a). The second reflection angle (204b) may depend on the second incident angle (203b).

[0022] In some embodiments, the reflection spectrum (202) may be approximately the same for all angles of incidence (203a to 203c). That is, the response of the structure (100) to the spectrum (100) may be angle-independent. Angle-independence may not be truly independent, that is, there may be some deviation in the exact peak wavelength reflected in the reflection spectrum (202) based on the angles of incidence (203a to 203c), but this angle dependence is greatly reduced compared to other metamaterials.

[0023] The reflected peak wavelength may vary slightly based on the angle of incidence (203a to 203c). For example, the spectrum (201) may be a broadband light ranging from 500 nm to 1000 nm. The first angle of incidence (203a) may be 30 degrees, the second angle of incidence (203b) may be 45 degrees, and the third angle of incidence (203c) may be 60 degrees. Correspondingly, the reflected spectrum (202) may have a first peak wavelength of about 600 nm for the first angle (203a), a second peak wavelength of about 602 nm for the second angle (203b), and a third peak wavelength of about 604 nm for the third angle (203c). The first peak wavelength, the second peak wavelength, and the third peak wavelength may be substantially similar to apply the term “angle-independent,” but there may still be small wavelength deviations in the reflection spectrum (202) based on the angle of incidence (203a to 203c).

[0024] In another embodiment, the peak wavelength for any given angle may change when the structure (100) is stretched or compressed. If the structure (100) is stretched or compressed, the reflection spectrum (202) may have a new peak wavelength different from the first peak wavelength. The difference between the new peak wavelength and the first peak wavelength may be used to infer a change in pressure, as described further below.

[0025] In another embodiment, the peak wavelength may change when the structure (100) is exposed to and / or comes into contact with a liquid or other material. The composition of the liquid or other material may be determined based on the change in the peak wavelength. If the structure (100) exposes the nanostructure (101) and a liquid or other material, such as a fluid, comes into contact with the nanostructure (101), the reflection spectrum (202) may have a different peak wavelength compared to the peak wavelength in the absence of the material. The difference between the second peak wavelength and the different peak wavelength may be used to infer information such as the presence of a specific material in contact with the structure (100), which may be discussed in more detail in the following description.

[0026] The structure (100) may also be polarization-independent. That is, the reflection spectrum (202) may be polarization-independent. For example, the spectrum (201) may have different transverse electric (TE) or transverse magnetic (TM) polarizations. That is, for any polarization of the spectrum (201), the reflection spectrum (202) is approximately the same.

[0027] FIG. 2b illustrates a side view (210) of a nanostructure (102a). There may be an x-axis and a z-axis illustrated along with a y-axis that enters the plane of the side view (210). The z-axis may illustrate the height of the nanostructure (102a), and the x-axis may illustrate the width of the nanostructure (102a). At the bottom of the z-axis, the nanostructure (102a) may be the widest point of the nanostructure (102a), which may be the diameter of the nanostructure (102a). The diameter of the nanostructure (102a) is defined as the intersection of the nanostructure (102a) and the base substrate on which the nanostructure (102a) is formed. A cross-section of the nanostructure (102a) may be illustrated along the zx plane. In some embodiments, the diameter of the nanostructure (102a) at the base of the nanostructure (102a) may be 200 nm, but may be another diameter between 10 nm and 2000 nm. The height of the nanostructure (102a) may be 100 nm, but may be another height between, for example, 36 nm and 168 nm.

[0028] The dimensions of the nanostructure (102a) may vary based on the target wavelength and the material used. Determining the diameter and height of the nanostructures for the target wavelength requires interpreting two variables (diameter and height), and if one varies within an acceptable range, the other will vary accordingly. In some embodiments, the height of the nanostructure (102a) may be between 12% and 56% of the first distance (104). In some embodiments, the diameter of the nanostructure (102a) may be between 40% and 80% of the first distance (104).

[0029] The height and diameter of the nanostructure (102a) may be determined by verifying the vertical-to-plane mode for a fixed lattice constant and by varying the height and diameter of the nanostructure (102a). There may be parameters f and r that may be used in conjunction with experimental tests to verify the vertical-to-plane mode and to determine a range of acceptable height and diameter values. The experiment may compare variables f and r defined as follows:

[0030] f = diameter of nanostructure (102a) / lattice constant (i.e., first distance (104)) and

[0031] r = height of nanostructure (102a) / diameter of nanostructure (102a)

[0032] Referring to FIG. 2c, there may be an experimental test (220) based on experimentally varying height and diameter values, which may compare variables f and r with fixed lattice constant values. The lattice constant values ​​may be determined based on the target wavelength, and the final height and diameter of the nanostructure (102a) may be determined based on the results of the test (220). The test (220) may reveal regions (221, 223) and may have a boundary line (222). The region (223) that may include the boundary line (222) may be a region where a vertical-to-plane mode exists and may allow for angle-independent behavior. Region (221) may be a region where a vertical-to-plane mode does not exist.

[0033] With respect to the height and diameter values ​​of the nanostructure (102a) within region (221), the incident angle of the spectrum (201) may cause a large change in the peak wavelength shift of the reflection spectrum (202), which will be described in more detail below in FIGS. 3 and FIGS. 7. With respect to the height and diameter values ​​of the nanostructure (102a) in region (223), however, the incident angle of the spectrum (201) may cause a small change in the peak wavelength shift of the reflection spectrum (202) compared to region (221). That is, the region (223) containing the boundary line (222) may cause angle independence or a less angle-dependent peak wavelength shift of the reflection spectrum (202).

[0034] Additionally, when performing measurements of the peak wavelength shift of the spectrum (202) for the vertical-to-plane (i.e., angle-independent) structure (100) of FIG. 1, it may be desirable to have a larger peak wavelength shift so that the results can be read more clearly from the sensor (600) described in FIG. 6 and 7. The further one moves from the boundary line (222) into the vertical-to-plane mode region, the less variation there is in the peak wavelength shift that may occur. The less variation there is in the peak wavelength shift that may occur, the more difficult it may be to perform the measurements. The angle-independent characteristics of the structure (100) may not change, but reading the measurements may be more difficult when the variation in peak wavelength is smaller.

[0035] Physical parameters of the height, diameter, and lattice constant of the nanostructure (102a) may affect the peak wavelength shift of the reflection spectrum (202). However, as long as the parameters enable a vertical-to-plane mode, there may be little to no difference in the measured peak wavelength shift due to the angle of incidence (unlike the values ​​found in region 221). Therefore, it may be advantageous to select a height and diameter that may be at the boundary line (222).

[0036] The lattice constant, the first distance (104), may be determined based on a target wavelength, which may be the peak wavelength reflected for the reflection spectrum (202), or may be approximately 1 / 2 of the target wavelength. For example, if the target wavelength is 620 nm, the lattice constant may be approximately 300 nm. For the diameter, height, and lattice constant values, a vertical-to-plane mode may be present to allow the reflection spectrum (202) to have a peak wavelength shift. In some ranges of f and r, the peak wavelength shift for the reflection spectrum (202) may be greater than for other ranges of f and r.

[0037] In some embodiments, the nanostructure (102a) may include gold, f may be in the range of 0.4 to 0.8, and r may be in the range of 0.3 to 0.7. Thus, f*r may be 0.3*0.4, i.e., 0.12, or 0.8*0.7, i.e., 0.56, providing a ratio of 12% to 56% of the height of the nanostructure (102a) for the first distance (104). In other examples, other ratios may exist. These embodiments may be for the visible spectrum of the spectrum (201). In another embodiment, the spectrum (201) may be near-infrared (NIR), and other metals may be used, including gold, silver, or aluminum.

[0038] In another embodiment, the nanostructure (102a) may have a cross-section in the zx plane that may be based on a parabolic shape, but other shapes including square, rectangular, spherical, trapezoidal, hemispherical, or other shapes may be used. The parabolic shape may be a quadratic surface having a single axis of symmetry (the z-axis in FIG. 2b), but the nanostructure (102a) may not be a perfect parabolic shape. There may be natural deviations due to physical constraints of manufacturing techniques, or it may not be a perfect parabolic shape by design.

[0039] The nanostructure (102a) may have a surface (205). The surface (205) may have a charge distribution (206). The surface (205) may have a surface plasmon (SP) mode, and the charge distribution (206) on the surface may oscillate periodically between positive and negative charges, which may be known as periodicity. This may occur along the surface (205) of the nanostructure (102a) and may be known as a vertical-to-plane mode, which may be a resonant oscillation of conduction electrons, which may be a refractive index (RI) perceived by waves on the surface (205). A gradual increase in RI along the z-axis may enable the vertical-to-plane mode.

[0040] Without being bound by theory, it is believed that there may be a polarized electric field along the z-axis, which may be denoted as Ez, as illustrated in FIG. 2b. Similarly, it is believed that there may be a polarized electric field along the x-axis, which may be denoted as Ex. There may be dipole moments obtained from the Ez or Ex electric field profiles. Ez may be oriented vertically, and Ex may be oriented parallel to the plane of periodicity of the pattern (103) on the structure (100). That is, Ez may follow the z-axis, and Ex may follow the x-axis. The dipole moments may be substantially less dependent on the angle of incidence (203a) of the spectrum (201) due to surface plasmon modes.

[0041] The vertical-to-plane mode may follow the z-axis and may be an SP mode in which the dipole moment of the nanostructure (102a) may be oriented perpendicular to the plane of periodicity regardless of the angle and polarization of the spectrum (201). As previously described, this may result in angle-independence and polarization-independence, but there may be some deviations in the response based on the angle and polarization. The deviations may be much smaller than for other nanostructure (102a) shapes and patterns (103) (which are non-parabolic), which will be further described in FIG. 3.

[0042] The nanostructure (102a) may have an effective plasmonic refractive index (the effective plasmonic RI) that varies based on the depth (z-axis) between the top and bottom of the nanostructure (102a). Along the z-axis from the top of the nanostructure (102a) to the bottom of the nanostructure (102a), there may be a gradual increase in the effective plasmonic refractive index. The effective plasmonic refractive index may be influenced by neighboring nanostructures (102a to 102f) of FIG. 1. As the first distance (104) between the two nanostructures increases, the refractive index may decrease. As the first distance (104) between the two nanostructures decreases, the refractive index may increase. Similarly, for two nanostructures, the bases of the nanostructures are closer to each other along the z-axis than the tops of the nanostructures. These differences in distance between the bottom and top of the two nanostructures may create an effective plasmon refractive index gradient (207). The effective plasmon refractive index gradient (207) may illustrate the relationship between depths from the top of the nanostructure (102a) to the base of the nanostructure (102a). The effective plasmon refractive index, neff, may be lower at the top of the nanostructure (102a) and may increase linearly along the surface (205) of the nanostructure (102a).

[0043] FIG. 3 illustrates an exemplary comparison of two different shapes of nanostructures (101) of FIG. 1. There may be an array of parabolic nanostructures (101) and an array of disk-shaped nanostructures (101), which will be described in more detail below. The shape of the nanostructures (101) may affect the change in wavelength dependence over a range of incident angles for input angles (203a to 203c). The parabolic array may include the parabolic nanostructures (101) of FIG. 1 and may represent a vertical-to-plane mode. The disk array may include the nanostructures (101) of FIG. 1 and may represent an out-of-plane mode.

[0044] The spectrum (201) of FIG. 2 may have an input angle range (203a to 203c), which may be illustrated between 25 and 60 degrees on the x-axis in the example currently illustrated. The spectrum (201) may interact with nanostructures (101) on the structure (100) and may result in a reflection spectrum (202) having a peak wavelength for each of the output angles (204a to 204c). The difference between the peak wavelengths of the reflection spectrum (202) in the spectrum (201) at angles of 25 degrees and higher than 25 degrees may be measured in units that may be nanometers, and is shown on the y-axis of FIG. 3. It can also be represented as λ.

[0045] In some embodiments, the first nanostructure type (301), which may be non-parabolic in shape, has a difference between the peak reflection spectrum (202) at angles of 25 degrees and higher than 25 degrees, and the peak spectrum (201) may vary linearly with the input angle range (203a to 203c). For each change of 5 degrees in the input angle, There may be a change of more than 10% in λ. That is, it may be known as an angle-dependent response There may be a change in λ. For example, for a fixed spectrum (201), the input angle (203a) may be 25 degrees. λ may be approximately 0 nm. The input angle (203b) may be 40 degrees. λ could be approximately 14 nm. The input angle (203c) could be 60 degrees. λ could be about 30 nm.

[0046] In another embodiment, the second nanostructure type (302) may have a parabolic shape and may have a much more angle-independent response to the disk-shaped structure of the second nanostructure type (101). Although there may still be an angle-dependent response to the second nanostructure type (302), the response may be very small compared to the first nanostructure type (301), and the term angle-independent may be used. For example, for a fixed spectrum (201), the input angle (203a) may be 25 degrees, and λ may be approximately 0 nm. The input angle (203b) may be 40 degrees, and λ may be approximately 1.4 nm. The input angle (203c) may be 60 degrees, and λ could be about 1.8 nm.

[0047] FIG. 4 illustrates a manufacturing process (400) for manufacturing a structure (100). FIG. 5 illustrates a process (500) of the manufacturing process (400). The manufacturing of the structure (100) may begin on a substrate (401).

[0048] The substrate (401) may be any metal on which the structure (100) is manufactured. In some embodiments, the substrate (401) may be made of silicon. The substrate (401) may be a silicon wafer.

[0049] A photoresist (402) may be deposited on a substrate (401). This may be the step of the process (501) of FIG. 5: depositing a photoresist (402) on a substrate (401). In some embodiments, the photoresist (402) may be about 1 micrometer (μm) thick. In other embodiments, the photoresist (402) may be 0.1 μm to 5 μm thick. In some embodiments, the photoresist (402) may be approximately uniform in thickness and flat across the substrate (401).

[0050] The photoresist (402) may include a light-sensitive polymer material that may be used in the process to form a patterned coating on a surface, and the patterning may include removing all of the unpatterned photoresist (402) from the surface.

[0051] The photoresist (402) may have an associated photosensitive agent and a solvent. In some embodiments, the photoresist (402) may be used in a positive or negative photoresist process. The chemical structures of the photoresist (402) may be photopolymerizable, photodegradable, photocrosslinkable, or any other photoresist structure. In another embodiment, the photoresist (402) may be exposed to electron beams.

[0052] In some embodiments, the photoresist (402) may be spin-coated onto the substrate (401) to form a uniformly thick layer. In some embodiments, the photoresist (402) may then be heated to 100°C to 120°C for 100 to 200 seconds.

[0053] The process (502) of FIG. 5 may include depositing a first metal (403) on a photoresist (402). The first metal (403) may also be referred to as a substrate metal. In some embodiments, a portion of the first metal (403) may also be deposited on a substrate (401) in addition to the photoresist (402). This may include an area between the edge of the substrate (401) and the edge of the photoresist (402). In another embodiment, all of the first metal (403) may be deposited on the photoresist (402).

[0054] In some embodiments, the first metal layer (403) may be nickel. In another embodiment, the first metal (4030) may be any other metal of the periodic table or an alloy of metals. In some embodiments, the first metal layer (403) may be 200 nm to 600 nm thick and may be used as a sacrificial layer. In some embodiments, the first metal layer (403) may be deposited using electron beam (e-beam) evaporation. In some embodiments, the evaporation rate of the first metal (403) may be 0.05 nm / s to 5 nm / s.

[0055] The process (503) of FIG. 5 may include depositing a resist (404) on a first metal layer (403). In some embodiments, the resist (404) may be a synthetic resin such as polymethyl methacrylate (PMMA). In other embodiments, the resist (404) may be a ZEON electron beam positive-tone (ZEP) resist commercially available and sold by ZEON SPECIALTY MATERIALS, INC. In other embodiments, the resist (404) may be any type of electron beam resist.

[0056] In some embodiments, the resist (404) may be spin-coated onto the first metal (403). In some embodiments, the baking time of the resist (404) may be between 100 seconds and 200 seconds. In some embodiments, the resist (404) may be baked between 150°C and 200°C.

[0057] In some embodiments, the resist (404) may have a thickness between 0.1 μm and 5 μm, but the thickness of the resist (404) may be greater or smaller and may depend on the target aspect ratio of the holes (405). The thickness of the resist (404) may also depend on manufacturing requirements such as the aspect ratio of the patterns formed on the resist (404).

[0058] In some embodiments, electron beam (e-beam) lithography may be applied to a resist (404) to form a pattern of holes to form the pattern (103) of FIG. 1. The process (504) of FIG. 5 may include the step of forming the pattern (103) on the resist (404). The electron beam lithography beam may be a 5 nA to 100 nA beam having a power intensity of 1000 μC / cc to 5000 μC / cc, or other values ​​greater than this range.

[0059] Electron beam lithography applied to the resist (404) may form holes (405). The holes (405) may expose a first metal (403) at the location of the holes (405). The pattern (103) of the holes (405) may be used to help form nanostructures (101). One of the holes (405) may have an aspect ratio which may be the ratio of the height of the hole to the diameter of the hole. In some embodiments, the aspect ratio may be 3 to 16.

[0060] In some embodiments, the diameter of one of the holes (405) may be 100 nm to 1 μm, but the diameter of the hole may be larger or smaller depending on the application of the target wavelength. In some embodiments, the diameter of the hole within the holes (405) may be within the order of the scale of the application of the target wavelength. In another embodiment, there may be diameters of the holes used in a plurality of holes (405).

[0061] In some embodiments, the layer (406) may be deposited on the first metal (403) at the locations of the holes (405). The process (505) of FIG. 5 may include the step of optionally depositing the layer (406) on the first metal (403). The layer (406) may be a metal such as chromium and may have a thickness of 1 nm to 5 nm. The layer (406) may also be known as an adhesive layer. The layer (406) may allow for better adhesion between the first metal (403) and the second metal (407).

[0062] The second metal (407) may be deposited on part or all of the layer (406) at the location of the holes (405), which may be at the same location as the pattern (103) or may form the pattern (103). The second metal (407) may also be referred to as a nanostructured metal. In another embodiment where the first metal (403) is not used, the second metal (407) may be deposited on any substrate at the location of the holes (405). The process (506) of FIG. 5 includes the step of depositing the second metal (407) at the location of the holes (405). In another embodiment, the second metal (407) may be deposited on the first metal (403) at the location of the holes (405) where the layer (406) is not present. In some embodiments, the second metal (407) may be gold, but may be aluminum, silver, copper, aluminum-doped zinc oxide, indium tin oxide, titanium nitride, indium gallium arsenide, tungsten oxide, titanium-tungsten, or any other metal or metal alloy. In some embodiments, the second metal (407) may have a thickness of 5 nm to 500 nm, but may have a different thickness depending on the application of the target wavelength. The application of the target wavelength may be a wavelength at which the nanostructure (101) interacts with the target wavelength, or a peak wavelength reflected in the reflection spectrum (202) of FIG. 2a. In some embodiments, the selected second metal (407) may depend on the target wavelength. For the visible spectrum, the second metal (407) may be gold, but may be other metals. For the near-infrared (NIR) spectrum, the second metal (407) may be aluminum or silver, but may be other metals. The spectral range reflected by the metal may be used to determine the metal to be selected for the target wavelength.While gold may reflect the visible spectrum, aluminum and silver may reflect the near-infrared spectrum.

[0063] In some embodiments, the second metal (407) may be deposited using electron beam deposition, but other deposition methods may also be used.

[0064] Once the second metal (407) is deposited, it may initially be in shape (408). In some embodiments, the shape (408) may be cone-shaped. The top of the cone may be flat or flat and may not end at a single point. The cone shape may be formed as a result of the aspect ratio of the holes (405). If the aspect ratio is low, the shape (408) may look like a disc. If the aspect ratio is high, the shape (408) may look more like a cone having a single point sharp at its tip. As described below, the forming of the second metal (407) from shape (408) to shape (409) may occur after the resist (404) is removed.

[0065] In some embodiments, the resist (404) may be removed. The process (507) of FIG. 5 includes a resist removal step (404). The resist (404) may be removed by a lift-off bath method using a solvent stripper such as REMOVER PG, which is commercially available and sold by KAYUKA ADVANCED MATERIALS. REMOVER PG may be used, and the resist (404) may be in the lift-off bath for 6 to 30 hours. In another embodiment, a different method may be used to remove the resist (404).

[0066] The second metal (407) may be in shape (408) or, in the absence of resist (404), may be deformed into shape (409). The process (508) of FIG. 5 may include a step of deforming the second metal (407) from shape (408) to shape (409). In some embodiments, the shape (409) may be parabolic. In another embodiment, the shape (409) may be a disk, a cone, or a hemisphere. In some embodiments, exposure to an ion beam may be used to form the second metal (407) from shape (408) to shape (409).

[0067] Focused-ion beam (FIB) exposure may be used to form the second metal (407) into a shape (409) with a beam of 0.1 nA to 2 nA, which may have a residence time of 0.01 ms (millisecond) to 1 ms. The residence time may be the exposure time of the ion beam to the second metal (407). The FIB may be a directional beam that may allow the edges of the second metal (407) of the shape (408) to be worn away. That is, the FIB may be directional, and in some embodiments, may be perpendicular to the substrate (401). Pointed features such as edges, points, or flat surfaces facing the FIB direction may be removed. In some embodiments, the direction of the ion beam may be at an angle between 0 degrees (parallel) and 90 degrees (perpendicular) with respect to the substrate (401). In some embodiments, the orientation may not change during the residence time in which the ion beam is exposed. In another embodiment, the orientation may change during the residence time in which the ion beam is exposed.

[0068] The process (509) of FIG. 5 may include the step of optionally depositing a surface (410) on the second metal (407). In some embodiments, the surface (410) may be PDMS and may be deposited via spin coating, but the surface (410) may be elastic or other materials that allow waves to travel through it and may be deposited by another technique. In some embodiments, the surface (410) may be 1 to 100 times the height of the second metal (407). In some embodiments, the surface (410) may be an optional surface and may not be deposited on the second metal (407).

[0069] In some embodiments, the first metal (403) may extend beyond the base of the photoresist (402). This extended region may be cut off, and the structure of the photoresist (402), the first metal (403), the layer (406) (if included in the deposition process), the second metal (407), and the surface (410) may be removed from the substrate (401). The photoresist (402) may then be removed using a solvent such as acetone. In some embodiments, the acetone solvent may be used for 2 to 10 minutes to remove the photoresist (402).

[0070] In some embodiments, where the structure (100) comprises nanostructures (101) inserted into the surface (410) of FIG. 1, the first metal (403) may be removed by an acid bath. The process (510) of FIG. 5 may include a step of removing the first metal (403). In some embodiments, there may be cuts on the sides of the first metal (403) exposing the photoresist (402) and (if present) the layer (404), and the acid bath may be used to remove the layers from bottom to top. That is, the photoresist layer (402) may be removed, then the layer (403), and then the layer (404), if present. Hydrochloric acid may be used, and the structure may be in the acid bath for 12 to 36 hours. In another embodiment, the first metal (403) may be removed by an alternative method. The resulting structure may be a structure (100) that may include a layer (406), a second metal (407), and a surface (410). In another embodiment, the layer (406) may also be removed using a hydrochloric acid bath.

[0071] In another embodiment, the first metal (403) and layer (402) may not be required, and the resulting structure may be fabricated directly on the substrate (401). Subsequently, processes (502) and (503) may not occur. Such an embodiment may be for a structure (100) on a surface of a substrate (401) where the nanostructures (101) are exposed and the surface (410) is absent. In this embodiment, process (510) may not occur, and an acid bath may not be used. Instead, the substrate (401) may be cut to form the structure (100).

[0072] The resulting structure may be a structure (100) that may include a second metal (407) and a surface (410).

[0073] In another embodiment, the structure (100) may include a metal (407) and a surface (410) when the layer (406) is not used.

[0074] FIG. 6 illustrates an exemplary embodiment of a sensor (600) in top view and side view. The sensor (600) may use a structure (100) to measure changes in pressure. The sensor (600) may include a cavity (601). A membrane (602) may be on the upper side of the cavity (601). The structure (100) may be on the membrane (602).

[0075] The cavity (601) may be an elastomeric material such as PDMS. The cavity (601) may be filled with a compressible fluid at a known pressure, such as air, or may be sealed so that the fluid does not penetrate the cavity (601) if it is submerged in the fluid. In some embodiments, the cavity (601) may be a cylinder having a height of 10 μm to 1 mm and a diameter of 100 μm to 5 mm. The structure (100) may be attached to the cavity (601) on the surface of the membrane (602) or inserted into the membrane (602).

[0076] In some embodiments, the membrane (602) may be deflected based on an external pressure difference relative to the inside. The spectrum (201) may be transmitted to a structure (100) which may be reflected into a reflection spectrum (202) that may have a reflected associated peak wavelength. The reflected peak wavelength in the reflection spectrum (202) of an unknown pressure may be compared to the observed peak wavelength when the pressure difference is known to determine the pressure change within the membrane (602).

[0077] Specifically, the cavity (601) may experience a pressure difference between the internal cavity (601) fluid and the external environment, which deflects the membrane (602). The deflection of the membrane (602) may cause radial strain on the structure (100), which may cause the nanostructures (101) inserted inside the structure (100) to be more or less densely spaced. This may eventually cause a change in the peak wavelength, which may be used to estimate the pressure difference, as described in FIG. 7. In some embodiments, the cavity (601) may be located in the anterior chamber of the eye, at a location that may be outside the field of view. Changes in intraocular pressure may eventually lead to changes in pressure in the cavity (601), which may cause the membrane (602) to be deflected and the structure (100) to be deflected.

[0078] While the previously described embodiments focus on pressure sensors using a structure (100) and a cavity (601), the structure (100) may also be used without the cavity (601). In another embodiment, the membrane (602) and the structure (100) may form a sensor without the cavity (601). The structure (100) may be inserted into the membrane (602) or positioned on top of the membrane (602). In the structure (100) inserted into the membrane (602), the resulting configuration may be used as a sensor for measuring the elongation or compression of a material when positioned on a surface. In the structure (100) positioned on top of the membrane (602), the resulting structure may be used to detect the composition of a material or liquid that is in direct contact with the structure (100) or positioned on top of the structure (100).

[0079] FIG. 7 illustrates a pressure measurement (700) of the sensor (600) of FIG. 6 having a structure (100). FIG. 7 may also compare the change in the peak wavelength of the reflection spectrum (202) at varying pressures for structures (100) having the first nanostructure type (301) and the second nanostructure type (302) of FIG. 3. FIG. 7 illustrates the advantages of using parabolic nanostructures. The x-axis represents the change in wavelength in nm | λ| can also be plotted. The y-axis can plot the reflectance of the reflection spectrum (202) in arbitrary units (au). Reflectance can be measured in the number of photons, which can be measured by a spectrometer. The number of photons may vary depending on the physical environment, light source power, and other variables. Therefore, arbitrary units may be used to analyze reflectance and compare peak wavelength shifts.

[0080] Changes in the peak wavelength of the reflection spectrum (202) for the first nanostructure type (301) at varying angles of incidence (203a to 203c) and varying pressure levels in FIG. 2a may be illustrated in response (701). Changes in the peak wavelength of the reflection spectrum (202) for the second nanostructure type (302) at varying angles of incidence (203a to 203c) and varying pressure levels in FIG. 2a may be illustrated in response (702). As described in FIG. 3, the first nanostructure type (301) may include disks or other non-parabolic shapes. The second nanostructure type (302) may include parabolic-shaped nanostructures.

[0081] FIG. 7 may illustrate three angles of incidence for the spectrum (201) of FIG. 2 in scenarios (710, 720, 730). In scenario (710), the angle of incidence may be 60 degrees. In scenario (720), the angle of incidence may be 45 degrees, and in scenario (730), the angle of incidence may be 30 degrees. Scenarios (710, 720, 730) may correspond to the input angles (203a to 203c) of FIG. 2, respectively.

[0082] For each of the scenarios (710, 720, 730) and for all of the responses (702, 701), there may be three sets of peak wavelength shifts corresponding to pressures of the sensor (600) of 0 mmHg (i.e., no pressure change), 20 mmHg, and 40 mmHg. For each of the three sets of graph lines, the top graph line may correspond to a pressure change of 0 mmHg, the middle graph line may represent a pressure change of 20 mmHg, and the bottom graph line may represent a pressure change of 40 mmHg. For example, measurement (702a) may show a peak wavelength shift for the second nanostructure type (302) when the sensor (600) is calibrated to a pressure change of 0 mmHg.

[0083] Referring to scenario (710), there are responses (702, 701) for an angle of incidence of 60 degrees. In response (702), which may correspond to a second nanostructure type (302) within scenario (710), there may be three profiles of corresponding peak wavelength shifts, illustrated in measurements (702a to 702c). Measurement (701a) may correspond to a pressure change of 0 mmHg. Measurement (701b) may correspond to a pressure change of 20 mmHg, and measurement (701c) may correspond to a pressure change of 40 mmHg.

[0084] Similarly, referring to scenario (710), for response (701), measurement (701a) may have a pressure change of 0 mmHg, measurement (701b) may have a pressure change of 20 mmHg, and measurement (701c) may have a pressure change of 40 mmHg.

[0085] Referring to the 0 mmHg pressure change of the response (702) across multiple angles of incidence corresponding to scenarios (710, 720, 730), there may be a peak wavelength shift (702a) in scenario (710), a peak wavelength shift (703) in scenario (720), and a peak wavelength shift (740) in scenario (730). The peak wavelength shift (702a) may be approximately 3 nm, the peak wavelength shift (703) may be approximately 2.75 nm, and the peak wavelength shift (704) may be approximately 2.5 nm.

[0086] Referring to the pressure change of 0 mmHg in response (701), there may be a peak wavelength shift (701a) in scenario (710), a peak wavelength shift (705) in scenario (720), and a peak wavelength shift (706) in scenario (730). The peak wavelength shift (701a) may be approximately 25 nm, the peak wavelength shift (705) may be approximately 18 nm, and the peak wavelength shift (706) may be approximately 15 nm. Examining other pressure changes (701, 702), it may be found that response (702) may have an angle-independent response (e.g., a very small peak wavelength shift) to the peak wavelength change of the spectrum (202). As previously described, angle independence may be lower than angle dependence in other solutions. The response (702), which may use parabolic-shaped nanostructures of the second nanostructure shape (302), may have a peak wavelength shift at 0 mmHg of 2.5 nm to 3 mm for angles of incidence ranging from 30 degrees in each scenario (730) to 60 degrees in scenario (710). The difference in peak wavelength shift between 30 and 60 degrees may be approximately 0.5 nm. In the visible spectrum, a difference of 0.5 nm in peak wavelength shift may not result in a color change. Therefore, if a parabolic-shaped nanostructure is used in the sensor (600), there may be an “angle-independent” range in which measurements may provide approximately the same reading over a range of angles of incidence.

[0087] Meanwhile, the response (701), which may use a first nanostructure type (301) using disk-shaped nanostructures, may exhibit an angle-dependent response to peak wavelength shifts (701a, 704, 706). The response (701) may have a peak wavelength shift at 0 mmHg between 15 nm and 25 nm for angles of incidence ranging from 30 degrees in scenario (730) to 60 degrees in scenario (710). The difference in peak wavelength shift for angles of incidence from 30 to 60 degrees may be approximately 10 nm. In the visible spectrum, a difference in peak wavelength shift of 10 nm may result in a color change. Thus, if disk-shaped nanostructures are used in the sensor (600), there may be an “angle-dependent” range in which measurements may provide different readings over a range of angles of incidence.

[0088] As previously described, parabolic-shaped nanostructures may be angle-independent or depend less on the angle of incidence, thus allowing for a useful sensor (600). The angle of incidence of the spectrum (201) may not need to be precise and may be a range of angles, such as from 30 to 60 degrees. This may be illustrated in the response (702). Unlike the responses (702), in the responses (701), there may be an angle-dependent response that may not be useful to the sensor (600) because the measurements may require a precise angle of incidence to provide repeatable measurements.

[0089] Pressure measurement readings may be calibrated for the sensor (600) by using pressure measurement data (700), specifically of the responses (702).

[0090] The sensor (600) may use parabolic-shaped nanostructures and may be calibrated with pressure measurements as shown in the responses (702). That is, for a given pressure change, there may be a single peak wavelength shift regardless of the angle of incidence of the spectrum (201). As shown in the shaded area of ​​the responses (702), the peak wavelength shift for each pressure change is different across the pressure and nearly identical across the angle of incidence. Thus, the previously difficult problem of measuring pressure across a range of angles of incidence may now be solvable and may be used in the sensor (600).

[0091] Exemplary embodiments of the concept of the present invention may be extended without limitation to the following descriptions:

[0092] Description 1: A metamaterial structure comprising a substrate and nanostructures positioned in a pattern on or within the substrate, wherein the nanostructures have a parabolic shape and are arranged in a periodic pattern.

[0093] Description 2: In Description 1, the nanostructures are operable in a vertical-to-plane mode, and the vertical-to-plane mode further comprises an angle-independent surface plasmon mode and a polarization-independent surface plasmon mode, a metamaterial structure.

[0094] Description 3: In Description 1, the nanostructures are metamaterial structures composed of one or more of gold, aluminum, silver, copper, aluminum-doped zinc oxide, indium / tin oxide, titanium nitride, indium gallium arsenide, tungsten oxide, or titanium-tungsten, or a combination thereof.

[0095] Description 4: In Description 1, the substrate is a metamaterial structure that is flexible or stretchable.

[0096] Description 5: A metamaterial structure in which the nanostructure shape of Description 1 is a semi-elliptical or parabolic shape.

[0097] Description 6: A metamaterial structure according to Description 1, wherein the nanostructures are arranged in a semi-periodic pattern including both equidistant nanostructures and non-equidistant nanostructures.

[0098] Description 7: A metamaterial structure according to Description 1, wherein the distance between the nearest nanostructures is 60 nm to 600 nm.

[0099] Description 8: A metamaterial structure according to Description 1, wherein the distance between the nearest nanostructures is 120 nm to 1200 nm.

[0100] Description 9: A metamaterial structure according to Description 1, wherein the diameter of the nanostructures is 10 nm to 2000 nm.

[0101] Description 10: A metamaterial structure according to Description 1, wherein the height of the nanostructures is 36 nm to 168 nm.

[0102] Description 11: A metamaterial structure in which the periodic pattern of Description 1 is a hexagon.

[0103] Description 12: A metamaterial structure in which the periodic pattern of Description 1 is a square.

[0104] Description 13: A method for manufacturing a metamaterial surface comprising the steps of depositing a nanostructured metal on a substrate and forming paraboloids from the nanostructured metal.

[0105] Description 14: A method for manufacturing a metamaterial surface according to Description 13, further comprising the step of depositing a resist before the step of depositing a nanostructured metal, and the step of forming a pattern of holes before the step of depositing a nanostructured metal.

[0106] Description 15: A method for manufacturing a metamaterial surface by depositing a flexible material surface on a nanostructured metal, in accordance with Description 13.

[0107] Description 16: A method for manufacturing a metamaterial surface according to Description 13, further comprising the step of depositing a substrate metal before the step of depositing a nanostructured metal, and the step of dissolving the substrate metal after the step of forming parabolic surfaces from the nanostructured metal.

[0108] Description 17: A method for manufacturing a metamaterial surface, wherein, in Description 16, the substrate metal has a thickness of 200 nm to 600 nm.

[0109] Description 18: A method for manufacturing a metamaterial surface according to Description 13, further comprising the steps of depositing a photoresist before depositing a nanostructured metal, and removing the photoresist after the nanostructured metal is deposited.

[0110] Description 19: A method for manufacturing a metamaterial surface according to Description 14, further comprising the step of depositing an adhesive layer before depositing a nanostructured metal.

[0111] Description 20: A method for manufacturing a metamaterial surface, wherein the adhesive layer is chromium, in Description 19.

[0112] Description 21: A method for manufacturing a metamaterial surface, wherein, in Description 14, the holes have an aspect ratio of 3 to 16.

[0113] Description 22: A method for manufacturing a metamaterial surface, wherein the nanostructured metal in Description 13 has a thickness between 50 nm and 500 nm.

[0114] Description 23: A method for preparing a metamaterial surface, wherein the nanostructured metal of Description 13 comprises one or more of gold, aluminum, silver, copper, aluminum-doped zinc oxide, indium / tin oxide, titanium nitride, indium gallium arsenide, tungsten oxide, or titanium-tungsten, or a combination thereof.

[0115] Description 24: A method for determining pressure changes, comprising the steps of accommodating a wavelength spectrum on a metamaterial structure, measuring a reflection peak wavelength from the metamaterial, and comparing the reflection peak wavelength with a reference point.

[0116] Description 25: A pressure sensor comprising a metamaterial and a cavity, wherein the metamaterial is located within a pattern, has a parabolic shape, and further comprises periodic nanostructures.

Claims

Claim 1 A metamaterial structure comprising: a substrate; and nanostructures positioned in a pattern on or within the substrate, wherein the nanostructures have a parabolic shape and are arranged in a periodic pattern, and each of the nanostructures comprises a nanostructure metal and a flexible material surface on the nanostructure metal. Claim 2 A metamaterial structure according to claim 1, wherein the nanostructures are operable in a normal-to-plane mode, and the normal-to-plane mode further comprises an angle-independent surface plasmon mode and a polarization-independent surface plasmon mode. Claim 3 In claim 1, the nanostructures are metamaterial structures composed of one or more of gold, aluminum, silver, copper, aluminum-doped zinc oxide, indium / tin oxide, titanium nitride, indium gallium arsenide, tungsten oxide, or titanium-tungsten, or a combination thereof. Claim 4 In claim 1, the substrate is a flexible or stretchable metamaterial structure. Claim 5 A metamaterial structure according to claim 1, wherein the shape of the nanostructures is hemi-ellipsoid or parabolic. Claim 6 A metamaterial structure according to claim 1, wherein the nanostructures are arranged in a semi-periodic pattern including both equidistant nanostructures and non-equidistant nanostructures. Claim 7 A metamaterial structure according to claim 1, wherein the distance between the closest nanostructures is 60 nm to 600 nm. Claim 8 A metamaterial structure according to claim 1, wherein the distance between the closest nanostructures is 120 nm to 1200 nm. Claim 9 A metamaterial structure according to claim 1, wherein the diameter of the nanostructures is 10 nm to 2000 nm. Claim 10 A metamaterial structure according to claim 1, wherein the height of the nanostructures is 36 nm to 168 nm. Claim 11 In claim 1, the periodic pattern is a hexagon, a metamaterial structure. Claim 12 In claim 1, the periodic pattern is a square, a metamaterial structure. Claim 13 A method for manufacturing a metamaterial surface, comprising the steps of: depositing a nanostructured metal on a substrate; forming parabolic surfaces from the nanostructured metal; and depositing a flexible material surface on the nanostructured metal. Claim 14 A method for manufacturing a metamaterial surface according to claim 13, further comprising: a step of depositing a resist before the step of depositing the nanostructured metal; and a step of forming a pattern of holes before the step of depositing the nanostructured metal. Claim 15 delete Claim 16 A method for manufacturing a metamaterial surface according to claim 13, further comprising: a step of depositing a substrate metal before the step of depositing the nanostructure metal; and a step of dissolving the substrate metal after the step of forming the paraboloids from the nanostructure metal. Claim 17 A method for manufacturing a metamaterial surface according to claim 16, wherein the substrate metal has a thickness of 200 nm to 600 nm. Claim 18 A method for manufacturing a metamaterial surface according to claim 13, further comprising: a step of depositing a photoresist before the nanostructured metal is deposited; and a step of removing the photoresist after the nanostructured metal is deposited. Claim 19 A method for manufacturing a metamaterial surface according to claim 14, further comprising the step of depositing an adhesive layer after the nanostructured metal is deposited. Claim 20 A method for manufacturing a metamaterial surface, wherein the adhesive layer is chromium, in claim 19. Claim 21 A method for manufacturing a metamaterial surface, wherein, in claim 14, the holes have an aspect ratio of 3 to 16. Claim 22 A method for manufacturing a metamaterial surface, wherein the nanostructured metal has a thickness of 50 nm to 500 nm in claim 13. Claim 23 A method for manufacturing a metamaterial surface according to claim 13, wherein the nanostructured metal comprises one or more of gold, aluminum, silver, copper, aluminum-doped zinc oxide, indium / tin oxide, titanium nitride, indium gallium arsenide, tungsten oxide, or titanium-tungsten, or a combination thereof. Claim 24 delete Claim 25 delete Claim 26 In claim 1, the pattern is a metamaterial structure comprising a triangular shape. Claim 27 In claim 26, the pattern is a metamaterial structure comprising an equilateral triangle shape. Claim 28 In claim 26, the pattern is a metamaterial structure comprising an isosceles triangle shape.

Citation Information

Patent Citations

  • Anti-reflective film having a nano structure and preparing process the same

    KR1020140122336A

  • Double nano structure with ultra low reflection in visible wavelength region

    KR1020140129450A

  • Metamaterial having a high refractive index, and method for preparing the same

    KR1020180054105A

  • Switchable optical elements

    US20130170018A1

  • Atomic layer deposition process for fabricating dielectric metasurfaces for wavelengths in the visible spectrum

    US20180341090A1